Hybrid Actor Capacity in Collaborative Governance - Nila Wahyuni; Desna Aromatica; Maryam Jamilah (Universitas Teuku Umar, 2023)
So far, studies conducted by scientists in the field of public administration have only grouped stakeholders or actors involved in collaborative forums into state and non-state stakeholders. Whereas in the contemporary era, many institutions were formed and were hybrid. Empirical facts in the field identify other forms outside the two entities that the researchers call hybrid actors, namely actors who act inside and outside the state system. One of the actors showing these characteristics in a collaborative forum is the Padang City Children's Forum (FORANDANG) in the Padang City Child-Friendly City Task Force (KLA). The Children's Forum is a children's organization formed and fostered by the government to bridge communication and interaction between the government and children. This makes the Children's Forum a top-down institution. However, on the other hand, this organization demands active participation and initiation from its members, who are more bottom-up in nature. This study aims to determine hybrid actors' capacity to carry out joint actions in the Padang City KLA Task Force collaborative forum. To find out this, this research was designed using descriptive qualitative research methods with informant selection techniques using purposive sampling. Data collection techniques were collected through interviews, observation, and documentation review. The results showed that FORANDANG's capacity as a hybrid actor in the KLA Task Force for the City of Padang needed to run optimally, as indicated by the four main components: procedures and institutional structure, leadership, knowledge, and resources.